The effect of changes in oil price and monetary stance on stock market performance - evidence from Bursa Malaysia - Abdul Razak, Abdul Hadi (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2015)
Link to publisher's homepage at http://ijbt.unimap.edu.my/